Employment Protection, Product Market Competition and Growth - Winfried Koeniger (Institute for the Study of Labor (IZA), 2002)
It is commonly argued that labor market institutions such as employment protection worsen an economy?s performance and particularly so, if product markets become more competitive. Empirical evidence, however, has difficulties to detect a robust negative correlation between employment protection and growth. We show in a model with step-by-step innovations that whether employment protection decreases incentives to innovate and thus productivity growth depends on the degree of product market competition. For reasonable parameter values product market deregulation fosters growth substantially more in the flexible than in the constrained economy.
Keywords: L1; J65; O31; 330; step-by-step innovations; firing cost; Schumpeterian growth; Arbeitsmarktflexibilisierung; Innovationswettbewerb; Wettbewerb; Neue Wachstumstheorie; Theorie